2007
DOI: 10.1074/jbc.m704861200
|View full text |Cite
|
Sign up to set email alerts
|

Leucine Carboxyl Methyltransferase-1 Is Necessary for Normal Progression through Mitosis in Mammalian Cells

Abstract: Protein phosphatase 2A (PP2A) is a multifunctional phosphatase that plays important roles in many cellular processes including regulation of cell cycle and apoptosis. Because PP2A is involved in so many diverse processes, it is highly regulated by both non-covalent and covalent mechanisms that are still being defined. In this study we have investigated the importance of leucine carboxyl methyltransferase-1 (LCMT-1) for PP2A methylation and cell function. We show that reduction of LCMT-1 protein levels by small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
78
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(93 citation statements)
references
References 55 publications
(54 reference statements)
12
78
2
Order By: Relevance
“…2A), thereby stabilizing the pathway. Previous work suggests PME-1 regulates the association of B/55a subunits with the PP2A core dimer (16,17) and that reduced methylation of PP2A results in decreased B/55a-PP2A formation (44,45). Our data suggest that PME-1 may affect the activity of B/56-dependent PP2A in the regulation of ERK or that B/55a-PP2A may also regulate ERK dephosphorylation.…”
Section: Discussionmentioning
confidence: 48%
“…2A), thereby stabilizing the pathway. Previous work suggests PME-1 regulates the association of B/55a subunits with the PP2A core dimer (16,17) and that reduced methylation of PP2A results in decreased B/55a-PP2A formation (44,45). Our data suggest that PME-1 may affect the activity of B/56-dependent PP2A in the regulation of ERK or that B/55a-PP2A may also regulate ERK dephosphorylation.…”
Section: Discussionmentioning
confidence: 48%
“…Cell Culture and Transfection-Wild type, hemizygous, and homozygous LCMT-1 knock-out MEFs were prepared from E14.5 or older mouse embryo torsos from a previously described gene-trap LCMT-1 knock-out mouse (23) and then cultured in Dulbecco's modified Eagle's medium (DMEM) supplemented with 10% fetal bovine serum, 1 mM sodium pyruvate, and nonessential amino acids at 37°C in 5% CO 2 . QBI293 (QBI-HEK-293 from QBiogene) cells were cultured in DMEM supplemented with 10% fetal bovine serum at 37°C in 10% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…1E (23). To examine whether this association is also compromised in MEFs isolated from LCMT-1 KO embryos and to quantitate the effect, B subunit/C subunit association was assayed by coimmunoprecipitation using cell lysates from LCMT-1 WT, hemizygous, and KO MEFs (Fig.…”
Section: Lcmt-1 Is the Major Methyltransferase For Pp4c And Pp6c-mentioning
confidence: 99%
See 1 more Smart Citation
“…However, a successful strategy based on this approach will likely require precise modulation of PME-1 or LCMT-1 activity. PP2A plays a number of critical functions in numerous cell types throughout the body (Janssens and Goris, 2001;Shi, 2009), and mice homozygous for a knock-out mutation of the murine PME-1 or LCMT-1 genes exhibit early postnatal or embryonic lethality respectively (Lee and Pallas, 2007;OrtegaGutierrez et al, 2008). Additionally, we observed that greater than 10 fold LCMT-1 over expression in second line of transgenic mice resulted in behavioral impairments on its own (data not shown).…”
Section: Discussionmentioning
confidence: 99%